Membaca Tragedi Lumpur Lapindo Dari Kacamata Fiqh Al-Biah - Muniri Muniri (Proceedings of Annual Conference for Muslim Scholars, 2017)
Gas exploration of lapindo caused environmentally damage and significant losses. Based on the chronology, it is categorizing as human error. There were some negligences during the exploration process. This study will focus on the chronology, causes and impact of the lapindo case. And this study will use fiqh al-bi>‘ah perspektive as tools analysis, with qualitative approach. Research findings reported, lapindo prefer to provide mas}lahah ha>jiyya>t and tahsi>niyya>t, rather than working on mas}lahah dharu>riyya>t. From the maslalah scope, the study found that the exploration mostly works on mas}lahah juz'iya>t (individual mas}lahah, and the certain group) and it is part of mas}lahah wahmi (fictitious advantage).